Outward Foreign Direct Investment in ASEAN - Sineenat Sermcheep; Lee, Cassey (Book collections on Project MUSE., 2017)
The level of outward foreign direct investment (OFDI) flows from ASEAN countries has increased rapidly in past two decades. This book examines OFDI trends and patterns in the ASEAN region including the impact of the ASEAN Economic Community. It also provides analyses of country policies affecting OFDI and the drivers of OFDI in Indonesia, Malaysia, Singapore and Vietnam. Myanmar is studied as an investment frontier for other ASEAN countries.